Border governance through local community empowerment: insights from Indonesia-Papua New Guinea borderline - Pakasi, Usman; Faridz, Muhammad; Majid, Hasbi; Susilawati, Susilawati (Otoritas : Jurnal Ilmu Pemerintahan, 2024)
This research explored the empowerment of local communities in governing the border areas between Indonesia and Papua New Guinea. The research aims at strategies to improve community livelihoods through the development of agricultural infrastructure, increased productivity, food security, and community participation in decision-making. The research methodology used was a qualitative case study conducted in Kampung Mosso, on the Indonesia-Papua New Guinea borderline. Data was collected through interviews with local leaders and local residents, complemented by a review of government reports and policies, NGO documents, and other academic sources. Analysis will utilize NVivo software for systematic coding and evaluation. Research findings showed that agricultural infrastructure development receives the highest allocation in community empowerment efforts, followed by education and training, and community participation. The research emphasizes the importance of a holistic approach that does not simply address direct outcomes such as increased productivity, but also focuses on sustainable human and institutional capacity building. The research highlights that effectively empowering local communities in border governance involves strategic investments in complementary infrastructure, education and participatory processes. Adopting a comprehensive approach, policymakers are able to empower border communities to sustainably process their resources, improve their livelihoods, and contribute positively to sustainable development goals in the border area.